jRDFa - browsing and visualization of linked data on the web - Carlomagno, André L.; Filho, Tito Gardel do Prado; Cerqueira, Marilton M.; Prazeres, Cássio V. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Several efforts in research and development of technologies have been spent to publish data in open standard formats. The main project in this regard is the Linked Open Data, which goal is to create an open and semantic Web of Data, enabling processing and understanding the data by software agents. However, not only the machines can take advantage of the explicit semantics of data. People can take advantage from the semantic of the data to explore unknown concepts, new relationships and to obtain personalized access to relevant resources and services. However, it is not trivial for a user without experience with Web of Data, to satisfactorily explore and use these data. This paper presents the jRDFa, an approach to support the web developer interested in presenting to non-technical users, semantic data embedded in HTML pages in RDFa format. This paper also presents two ways of presenting data in RDFa that were created using the jRDFa: tooltips visualization and facets navigation. To evaluate the proposed approach, this paper presents results of experiments on HTML pages with embedded jRDFa.